Perbandingan Perubahan Luas Luka dan Angiogenesis pada Luka Bakar Derajat IIB Tikus Sprague Dawley yang Diberikan Advanced Platelet-rich Fibrin dan Advanced Platelet-rich Fibrin Plus - Ellia Stella; Komang Ardi Wahyuningsih (Jurnal Kesehatan Andalas, 2021)
Platelet-rich fibrin (PRF) has a lot of benefits in the process of healing. The new generation of PRF, namely advanced PRF plus (A-PRF+), has a different fibrin structure and more growth factors compared to Advanced PRF (A-PRF), the generation before A-PRF+. Objectives:To compared the effects of A-PRF and A-PRF+ on the IIB degree burn. Methods: This experimental study used 20 male Sprague Dawley rats. All rats were given IIB degree burn and divided into four groups. Group 1 was treated with saline, Group 2 was treated with silver sulfadiazine 1%, Group 3 was treated with A-PRF, and Group 4 was treated with A-PRF+. Wound size reduction will be calculated every two days and measured with ImageJ and the wound would be made into a histological slide on day 14 to calculate angiogenesis. Results: Changes in the wound surface area for the group that was given A-PRF dan A-PRF+ are 2,333cm and 4,827cm. The wound surface area’s data were analyzed using Kruskal-Wallis and the results are statistically not significant (p>0,05). The number of angiogenesis for the group that was give A-PRF and A-PRF+ as followed are 5,88 and 4,867. The angiogenesis data were analyzed using one-way ANOVA and the results are statistically not significant (p>0,05). Conclusion: There is no difference between the effect of A-PRF and A-PRF+ towards changes in wound surface area and angiogenesis in IIB degrees burn wounds.Keywords:  A-PRF, A-PRF+, burn wound, angiogenesis, wound surface area